Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Adaptive decoupling control of key water quality parameters in wastewater treatment processes - Yanping Yao; Xianjun Du; Shengyi Cheng (Journal of Water Process Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Toward precise layer control of chemical vapor deposition growth of graphene films: from graphene to graphite - Runhan Xiao; Yangjian Xu; Chuang Tian; Jiawen Liu; Jie Cheng; Yanping Sui; Zhiying Chen; Shujie Tang; Guanghui Yu (Chemical Engineering Journal, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Complete genome sequence of a new victorivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Zhi Zhou; Huang Huang; Du Hai; Jiatao Xie; Jiasen Cheng; Yanping Fu; Daohong Jiang (Archives of Virology, 2026)

Quantifying heavy metal(loid)s sources in subtropical soils and assessing key determinants of their bioavailability: insights from the Yangtze River Delta, China - Minqi Shi; Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2026)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Translocation coefficients of heavy metals in the soil-rice system and their environmental implication - Cheng Wang; Minqi Shi; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Aquaporin ZmPIP2;4 promotes tolerance to drought during arbuscular mycorrhizal fungi symbiosis - Ying Ni; Hui Bao; Ruifan Zou; Yanping Wang; Kailing Xie; Beijiu Cheng; Xiaoyu Li (Plant and Soil, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

A study on the structure-functionality relationship of Solenaia oleivora protein under high-intensity ultrasonication processing - Wanwen Chen; Wu Jin; Xueyan Ma; Haibo Wen; Yanping Li; Gangchun Xu; Pao Xu; Hao Cheng (Food Chemistry, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

A numerical method for two-dimensional transient nonlinear convection-diffusion equations - Xiangyuan Meng; Mei Huang; Boxue Wang; Xiaoping Ouyang; Yanping Huang; Denggao Chen; Yanting Cheng; Yaodi Li (Annals of Nuclear Energy, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Genome-wide identification of nitrate transporter 1/peptide transporter family (NPF) induced by arbuscular mycorrhiza in the maize genome - Qiang Xu; Yanping Wang; Wen Sun; Yuanhao Li; Yunjian Xu; Beijiu Cheng; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Divergent temporal changes of heavy metals in the soil induced by natural versus anthropogenic forces: A case study in the Yangtze River delta area, China - Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Science of The Total Environment, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

Fractionations of heavy metals and their correlations with magnetic susceptibility in soil from a typical alluvial island in the lower yangtze river, China - Cheng Wang; Rong Ma; Jianhua Wang; Cong Zhong; Yanping Zhao; Patrick Browne (Journal of Cleaner Production, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

First kinetics verification of the useful H2Ogas inhibition on the thermal regeneration of spent activated carbon in flue gas desulfurization - Hanyu Deng; Wenzhen Cai; Lanhe Zhang; Yanping Jia; Xiaoqiang Wang; Qing Zong; Guishi Cheng; Xiaoying Hu; Changqing Dong; Ying Zhao (Fuel, 2023)

An improved zigzag-type printed circuit heat exchanger for supercritical CO2 Brayton cycles - Shenghui Liu; Cheng Gao; Minyun Liu; Yunxuan Chen; Jia Tang; Yanping Huang; Xiaoliang Zhu; Tianyang Xing (Annals of Nuclear Energy, 2023)

Auxin and CmAP1 regulate the reproductive development of axillary buds in Chinese chestnut (Castanea mollissima) - Yunhe Cheng; Lili Cheng; Guanglong Hu; Xiaomeng Guo; Yanping Lan (Plant Cell Reports, 2022)

Impact of waste of COVID-19 protective equipment on the environment, animals and human health: a review - Sheng Yang; Yanping Cheng; Tong Liu; Shaoping Huang; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Chemistry Letters, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Characterization of a newly identified RNA segment derived from the genome of Sclerotinia sclerotiorum reovirus 1 - Jichun Jia; Fan Mu; Yanping Fu; Jiasen Cheng; Yang Lin; Daohong Jiang; Jiatao Xie (Archives of Virology, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Characterization of a novel botoulivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Fan Mu; Jichun Jia; Yunxiang Xue; Daohong Jiang; Yanping Fu; Jiasen Cheng; Yang Lin; Jiatao Xie (Archives of Virology, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

A semi-supervised learning method for hyperspectral imagery based on self-training and local-based affinity propagation - Haimiao Ge; Haizhu Pan; Liguo Wang; Cheng Li; Yanzhong Liu; Wenlong Zhu; Yanping Teng (International Journal of Remote Sensing, 2021)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Characterization of a novel RNA virus from the phytopathogenic fungus Leptosphaeria biglobosa related to members of the genus Mitovirus - Yong Wang; Zhiyong Xu; Jiasen Cheng; Yanping Fu; Daohong Jiang; Jiatao Xie (Archives of Virology, 2019)

The complete chloroplast genome sequence of Actinidia kolomikta from north China - Yanping Lan; Lili Cheng; Wugang Huang; Qingchang Cao; Zhijun Zhou; Anjin Luo; Guanglong Hu (Conservation Genetics Resources, 2018)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Determination of Fatty Acid Composition and Phospholipid Molecular Species of Large Yellow Croaker ( Pseudosciaena crocea ) Roe from China - Peng Liang; Xinwei Cheng; Yanping Xu; Wenjian Cheng; Lijiao Chen (Journal of Aquatic Food Product Technology, 2017)

The complete chloroplast genome sequence of the endangered Chinese endemic tree Corylus fargesii - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Xueqiang Wang; Wugang Huang (Conservation Genetics Resources, 2017)

Complete genome sequence of a novel mitovirus from the phytopathogenic fungus Rhizoctonia oryzae-sativae - Assane Hamidou Abdoulaye; Jiasen Cheng; Yanping Fu; Daohong Jiang; Jiatao Xie (Archives of Virology, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

The complete chloroplast genome sequence of Corylus chinensis Franch - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Wugang Huang (Conservation Genetics Resources, 2017)

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans - Xiaoxiang Yang; Hui Cui; Jiasen Cheng; Jiatao Xie; Daohong Jiang; Tom Hsiang; Yanping Fu (Environmental Microbiology, 2016)
Summary Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

Characterization of porcine skeletal α-actin gene promoter: expression specificity and regulatory elements - Yujie Zhang; Xu Zhang; Nini Cheng; Yanping Li; Jinyi Xing (Genes & Genomics, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Joint toxicity of tetracycline with copper(II) and cadmium(II) to Vibrio fischeri: effect of complexation reaction - Fei Tong; Yanping Zhao; Xueyuan Gu; Cheng Gu; Charles C.C. Lee (Ecotoxicology, 2015)

Fruit skin color and the role of anthocyanin - Emrul Kayesh; Lingfei Shangguan; Nicholas Kibet Korir; Xin Sun; Nadira Bilkish; Yanping Zhang; Jian Han; Changnian Song; Zong-Ming Cheng; Jinggui Fang (Acta Physiologiae Plantarum, 2013)

Identification of microRNA-like RNAs in a plant pathogenic fungus Sclerotinia sclerotiorum by high-throughput sequencing - Jiahong Zhou; Yanping Fu; Jiatao Xie; Bo Li; Daohong Jiang; Guoqing Li; Jiasen Cheng (Molecular Genetics and Genomics, 2012)